Development of Reconfigurable Antenna for Advanced Tracking Technology - N. M. Sahar; M. T. Islam; N. Misran; M. R. Zaman (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper focuses on the design and fabrication of reconfigurable multiband antenna for RFID and GPS as an advance tracking technology for various applications that achieve a physically compact, planar profile and sufficient bandwidth. The antenna can be reconfigured as single band at 1.275 GHz for GPS applications when the switches are OFF state and dual-band frequencies at 0.915 GHz and 2.4 GHz required in RFID applications when the switches are ON state. The performance of the antenna involves changing the switches to ON or OFF mode by controlling RF switches. RF MEMs RMSW101, Single Pole Single Throw (SPST) switches have been chosen due to the satisfactory RF properties includes low insertion loss, good impedance matching and high isolation. The gain for single and dual band is greater than 2dBi. The design methodology and antenna measurement results are both presented and discussed in this letter.